Pengaruh Model Pembelajaran Problem Solving terhadap Hasil Belajar Seni Budaya Sub Bidang Studi Seni Rupa Siswa Kelas VIII SMP Negeri 21 Padang - Yumadiska Rahmadani, Dr. Ramalis Hakin, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2016)
This study aims to determine the results studied art students taught using problem solving learning model is different compared with the results studied art students taught using conventional teaching methods. Hypothesis tested in this study is result of learning. Type of study is a quasi-experiment. Data collection was done through achievement tets is a test article ( theory ), a test used to be seen fist difficulty indek, distinguishing, and rehabilitation. Findings showed that; the learning outcomes of students in learning art taught using problem solving learning model is different from the learning outcome of students taught using conventional teaching methods. This is shown from the calculation of statistical tets used was the t-test which saw the average calculated in the same group with a level of 95%.Kata kunci : hasil belajar, pembelajaran Seni rupa, model pembelajaran Problem Solving.